1979
DOI: 10.1002/cpt1979255part1536
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of beta adrenoreceptor antagonist drugs assessed by histamine bronchial provocation

Abstract: In a double-blind, within-patient, randomized study, 12 mild asthmatics were given single oral doses of propranolol (80 mg), metoprolol (100 mg), timolol (10 mg), or placebo. Resting heart rate and forced expiratory volume in one sec (FEV J were measured before and 90 min after treatment. Nonspecific bronchial reactivity was measured by inhaled histamine at 90 min. Following each active drug, resting heart rate changed to a similar extent and to a greater degree than after placebo (p < O.OJ). Changes in FEV 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
2
9
1
1
Order By: Relevance
“…The difference between the results of these authors and those reported here is probably attributable to differences in the sensitivities of the patients participating in the two studies. In contrast to the present study where a histamine concentration of 7.4 mg/ml was necessary to reduce FEV1 by 20% in the pretreatment period, in their patients, Ruffin et al (1979) were able to illicit the same response with a histamine concentration of 3.7 mg/ml.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…The difference between the results of these authors and those reported here is probably attributable to differences in the sensitivities of the patients participating in the two studies. In contrast to the present study where a histamine concentration of 7.4 mg/ml was necessary to reduce FEV1 by 20% in the pretreatment period, in their patients, Ruffin et al (1979) were able to illicit the same response with a histamine concentration of 3.7 mg/ml.…”
Section: Methodscontrasting
confidence: 99%
“…In similar experiment in which a larger dose of propranolol (80 mg) was used, Ruffin et al (1979) found that the histamine concentration needed to produce a 20% reduction in FEV1 was 47.8% lower than that necessary before treatment. The difference between the results of these authors and those reported here is probably attributable to differences in the sensitivities of the patients participating in the two studies.…”
Section: Methodsmentioning
confidence: 95%
“…Nicolaescu et al (1972) showed that treatment with propranolol and the cardioselective drug, practolol, produced a similar degree of potentiation of acetylcholine bronchospasms in their patients and they therefore proposed that the increased sensitivity might not be due to P-adrenoceptor blockade. In a more extensive double blind study, Ruffin, Frith, Anderton, Kumana, Newhouse & Hargreave (1979) compared the effects of propranolol on histamine bronchoconstriction with those of the Pl-selective drugs, metoprolol and timolol. The drugs were given in equivalent cardiac blocking doses, assessed from heart rate measurements, yet despite the corresponding differences in their P2-antagonistic properties, all three enhanced histamine responses to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, differences in the degree of selectivity of the cardioselective ,-adrenoceptor blockers since they displace to varying extents the bronchial dose-response curves to 32-adrenoceptor stimulants. In clinical studies, atenolol or bisoprolol appeared to be more selective than other compounds, such as acebutolol, metoprolol or oxprenolol (Greefhorst & van Herwaarden, 1982;Gribbin et al, 1981;Lammers et al, 1984;Lawrence et al, 1982;Macquin-Mavier et al, 1988;Perks et al, 1978;Ruffin et al, 1979;Tattersfield et al, 1984). Bronchial rings from a segmental bronchus were prepared and suspended in parallel in Krebs solution under an initial tension of 2.5 g. After 1.5 h of equilibration, the resting tension was between 1 and 2 g. Tensions were measured isometrically with strain gauges, amplifiers and .O.S..-Moise 2 recorder system (Celaster, Celle l'Evescault, 86600 Lusignan, France) (Advenier et al, 1986).…”
Section: Introductionmentioning
confidence: 99%